The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2024
DOI: 10.1186/s12964-023-01433-5
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between proteasome inhibitors and NF-κB pathway in leukemia and lymphoma: a comprehensive review on challenges ahead of proteasome inhibitors

Mahdi Pakjoo,
Seyed Esmaeil Ahmadi,
Mohammad Zahedi
et al.

Abstract: The current scientific literature has extensively explored the potential role of proteasome inhibitors (PIs) in the NF-κB pathway of leukemia and lymphoma. The ubiquitin-proteasome system (UPS) is a critical component in regulating protein degradation in eukaryotic cells. PIs, such as BTZ, are used to target the 26S proteasome in hematologic malignancies, resulting in the prevention of the degradation of tumor suppressor proteins, the activation of intrinsic mitochondrial-dependent cell death, and the inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 262 publications
1
0
0
Order By: Relevance
“…This impairment is associated with a significant inflammatory response revealed by injury of the endothelial cells with leukocyte infiltration and elevation of the inflammatory cytokines; IL-1 β, IL-6, and Tnf-α [72,73 and 65]. Consistent with the previous studies, the current work demonstrated the elevation of the inflammatory mediators; IL-1 β, Tnf-α, NF-ҡβ, and apoptotic factor; caspase 3 with a decrease of the antiapoptotic factor; Bcl2 in DOX-treated group as documented by Wang et al [48] and Pakjoo et al [74]. On the other hand, the L-carnitine-pretreated MSCs group showed the optimum results in decreasing the measured inflammatory, apoptotic, and fibrotic cytokines, and antiapoptotic Bcl2 elevation producing improvement of the structural architecture of cardiac muscles.…”
Section: Discussionsupporting
confidence: 90%
“…This impairment is associated with a significant inflammatory response revealed by injury of the endothelial cells with leukocyte infiltration and elevation of the inflammatory cytokines; IL-1 β, IL-6, and Tnf-α [72,73 and 65]. Consistent with the previous studies, the current work demonstrated the elevation of the inflammatory mediators; IL-1 β, Tnf-α, NF-ҡβ, and apoptotic factor; caspase 3 with a decrease of the antiapoptotic factor; Bcl2 in DOX-treated group as documented by Wang et al [48] and Pakjoo et al [74]. On the other hand, the L-carnitine-pretreated MSCs group showed the optimum results in decreasing the measured inflammatory, apoptotic, and fibrotic cytokines, and antiapoptotic Bcl2 elevation producing improvement of the structural architecture of cardiac muscles.…”
Section: Discussionsupporting
confidence: 90%